Functional activity of the oral endothelium in persons, with chronic periodontitis during treatment with plasmolifting - A. A. Fefelov; N. N. Tsybikov; L. F. Sholokhov; E. V. Fefelova (Acta Biomedica Scientifica, 2023)
Chronic periodontitis as an osteoimmune disease of the oral cavity is accompanied by a change in the functional activity of endotheliocytes. Moreover, abnormal vascularization exacerbates periodontal inflammation, as it promotes the transmigration of a larger number of immunocompetent cells, the influx of inflammatory mediators and cytokines.The aim of our work was to study the functional activity of the endothelium of the vessels of the oral cavity in persons suffering from chronic periodontitis in the treatment of plasmolifting.Materials and methods. Under observation were 30 patients diagnosed with chronic generalized periodontitis of moderate severity at the age of 35 (32.50; 40.00) years, with no severe somatic pathology (main group). The comparison group included 20 people aged 38 (34.00; 45.00) years with no inflammatory diseases in the oral cavity. All patients underwent local anti-inflammatory therapy and sanitation of periodontal pockets, correction of occlusal contacts, curettage, plasma lifting. Oral fluid concentration of soluble adhesion molecules ICAM-1 and VCAM-1, endothelin-1, qualitative and quantitative composition of microflora were determined.Results. After the treatment with plasmolifting, a noticeable relief of the activity of the inflammatory process was observed. In patients with chronic periodontitis, Porphyromonas gingivalis was found in 100 % of cases in a titer of 5.73 (4.9; 6.7) lg (gEq/sample), in 62.5 % – Prevotella intermedia in a titer of 4.5 (3.0; 5.5) lg (gEq/sample). Against the background of therapy, decrease of the occurrence of the microorganism and of the number of microorganisms was observed. The concentration of the soluble form of VCAM-1 in the oral fluid of patients with chronic periodontitis exceeded the values of the control group by 38.3 times (p = 0.000001), and ICAM-1 – by 18.1 times (p = 0.00001). Against the background of plasmolifting therapy, the level of the studied substances decreased, but exceeded the control values by 25.2 and 6.4 times, respectively. The content of endothelin in the oral fluid in patients with periodontitis exceeded the values of healthy individuals by 40.7 % (p = 0.003), during therapy its values decreased, but did not reach the level of healthy volunteers (p = 0.04).